PERAN MAJELIS TAKLIM DALAM MENANAMKAN NILAI-NILAI KEISLAMAN KEPADA MASYARAKAT (Studi pada Majelis Taklim Al-Marhamah RT 03 RW 03 Kelurahan Karadenan Kecamatan Cibinong Kabupaten Bogor Tahun 2018) - Kurniawan, Deni; Wahidin, Unang; Priyatna, Muhamad (Prosa PAI : Prosiding Al Hidayah Pendidikan Agama Islam, 2019)
Majelis taklim is one of the non formal diniyah educational institutions which aims to increase faith and devotion to Allah and noble character for the congregation, as well as realize the grace of the universe. The Taklim Council has a strategic function in fostering Muslims. These functions, among others, as a means of delivering religious messages, as a forum for exchanging information between worshipers in the religious field, as a forum for fostering intimacy and worship, and as a forum for information and cooperation among people.This research is a qualitative research which discusses the role of the taklim assembly in instilling Islamic values to the society (a study of the Taklim Al-Marhamah Assembly RT 03 RW 03 Karadenan Village Cibinong District, Bogor.The type of research that researchers do is descriptive qualitative research that is inductive in nature and is aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of individuals individually and in groups.The strategy applied in this study is the case study with the object that becomes this research is the community (society). Data collection is done by using observation, interview, and documentation methods. While in the technical analysis of data using qualitative methods and interpreting the data so that it can be used to draw conclusions.The results of the study showed that the Majelis Taklim Al-Marhamah had a very important role in instilling Islamic values to the people of RT 03 RW 03 Karadenan Village, Cibinong District, Bogor. Keyword: majelis taklim, Islamic values, Islamic society.